Cortical microinfarcts on 3T MRI: Clinical correlates in memory‐clinic patients. Issue 12 (5th May 2015) - van Veluw, Susanne J.; Hilal, Saima; Kuijf, Hugo J.; Ikram, Mohammad Kamran; Xin, Xu; Yeow, Tan Boon; Venketasubramanian, Narayanaswamy; Biessels, Geert Jan; Chen, Christopher
Abstract: Introduction: This is the first study to assess cerebral microinfarcts (CMIs) on 3 tesla (3T) magnetic resonance imaging (MRI) in a memory clinic population. Methods: We included 238 consecutive patients (aged 72.5 ± 9.1 years) from a memory clinic in Singapore. All patients underwent extensive neurological and neuropsychological testing and 3T MRI on the same day. Cortical CMI rating criteria were adapted from a previous study on 7T MRI. We analyzed the frequency and association of cortical CMIs with demographic, clinical, cognition, and other MRI findings. Results: Seventy‐five patients (32%) had cortical CMIs (median 1, range 1–43). Patients with CMIs showed worse cognitive functioning on MMSE, and in the domains of language and visuoconstruction. The presence of CMIs was related to other markers of small vessel disease, but most strongly larger cortical infarcts. Patients with CMIs were more often diagnosed with vascular dementia. Discussion: Cortical CMIs on 3T MRI are a novel marker of cerebrovascular disease in dementia.